Graphene-Multiwalled Carbon Nanotube Hybrids Synthesized by Gamma Radiations: Application as a Glucose Sensor. (1st June 2014) - Shahriary, Leila; Ghourchian, Hedayatollah; Athawale, Anjali A.
Abstract : Three-dimensional hybrid nanomaterial of graphene-multiwalled carbon nanotubes (G-MWCNTs) was synthesized using gamma rays emitted by a 60 Co source with a dose rate of 3.95 Gy min −1 . The products were characterized by fourier transform infrared (FTIR), ultraviolet-visible (UV-Vis), photoluminescence (PL), and micro-Raman spectroscopy, X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). FTIR and UV-Vis analysis reveals the formation of hybrid nanomaterial which is confirmed by XRD, micro-Raman analysis, and PL. SEM micrograph depicts the composite structure of graphene layers and MWCNTs, while the TEM micrograph exhibits graphene layers covered by MWCNTs. The G-MWCNTs hybrid used as electrode for electrochemical studies in K3 Fe(CN)6 shows enhancement in electrocatalytic behavior, compared to each individual starting material, therefore, has been applied for amperometric sensing of glucose in alkaline solution and exhibits sensitivity of 12.5 μ AmM -1  cm −2 and low detection limit 1.45 μ M (S / N = 3 ) in a linear range of 0.1 to 14 mM (R 2 = 0.985 ).